Male-killing mechanisms vary between Spiroplasma species - Arai, Hiroshi; Inoue, Maki N.; Kageyama, Daisuke (Frontiers in Microbiology, 2022)
Male-killing, a male-specific death of arthropod hosts during development, is induced by Spiroplasma (Mollicutes) endosymbionts of the Citri-Poulsonii and the Ixodetis groups, which are phylogenetically distant groups. Spiroplasma poulsonii induces male-killing in Drosophila melanogaster (Diptera) using the Spaid toxin that harbors ankyrin repeats, whereas little is known about the origin and mechanisms of male-killing induced by Spiroplasma ixodetis. Here, we analyzed the genome and the biological characteristics of a male-killing S. ixodetis strain sHm in the moth Homona magnanima (Tortricidae, Lepidoptera). Strain sHm harbored a 2.1 Mb chromosome and two potential plasmids encoding Type IV effectors, putatively involved in host–symbiont interactions. Moreover, sHm did not harbor the spaid gene but harbored ten ankyrin genes that were homologous to those in other S. ixodetis strains. In contrast to the predominant existence of S. poulsonii in hemolymph, our quantitative PCR assays revealed a systemic distribution of strain sHm in H. magnanima, with particularly high titers in Malpighian tubules but low titers in hemolymph. Furthermore, transinfection assays confirmed that strain sHm can infect cultured cells derived from distantly related insects, namely Aedes albopictus (Diptera) and Bombyx mori (Lepidoptera). These results suggest different origins and characteristics of S. ixodetis- and S. poulsonii-induced male-killing.